Population genetic analysis of Chadian Guinea worms reveals that human and non-human hosts share common parasite populations. - Elizabeth A Thiele; Mark L Eberhard; James A Cotton; Caroline Durrant; Jeffrey Berg; Kelsey Hamm; Ernesto Ruiz-Tiben (Public Library of Science (PLoS), 2018)
Following almost 10 years of no reported cases, Guinea worm disease (GWD or dracunculiasis) reemerged in Chad in 2010 with peculiar epidemiological patterns and unprecedented prevalence of infection among non-human hosts, particularly domestic dogs. Since 2014, animal infections with Guinea worms have also been observed in the other three countries with endemic transmission (Ethiopia, Mali, and South Sudan), causing concern and generating interest in the parasites' true taxonomic identity and population genetics. We present the first extensive population genetic data for Guinea worm, investigating mitochondrial and microsatellite variation in adult female worms from both human and non-human hosts in the four endemic countries to elucidate the origins of Chad's current outbreak and possible host-specific differences between parasites. Genetic diversity of Chadian Guinea worms was considerably higher than that of the other three countries, even after controlling for sample size through rarefaction, and demographic analyses are consistent with a large, stable parasite population. Genealogical analyses eliminate the other three countries as possible sources of parasite reintroduction into Chad, and sequence divergence and distribution of genetic variation provide no evidence that parasites in human and non-human hosts are separate species or maintain isolated transmission cycles. Both among and within countries, geographic origin appears to have more influence on parasite population structure than host species. Guinea worm infection in non-human hosts has been occasionally reported throughout the history of the disease, particularly when elimination programs appear to be reaching their end goals. However, no previous reports have evaluated molecular support of the parasite species identity. Our data confirm that Guinea worms collected from non-human hosts in the remaining endemic countries of Africa are Dracunculus medinensis and that the same population of worms infects both humans and dogs in Chad. Our genetic data and the epidemiological evidence suggest that transmission in the Chadian context is currently being maintained by canine hosts.